2010
DOI: 10.1159/000313693
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Surgical Outcome Scores according to ISGPS Definitions in Patients Undergoing Pancreatic Resection

Abstract: Aims: To evaluate the role of the Physiological and Operative Severity Score for the enUmeration of Mortality and Morbidity (POSSUM), the Portsmouth variant (p-POSSUM) and the Glasgow Prognostic Score (GPS) in predicting outcome after pancreatic surgery with reference to the International Study Group of Pancreatic Surgery (ISGPS) definitions of post-pancreatectomy complications. Methods: All consecutive patients undergoing major pancreatic resection over a 32- month period were included. POSSUM, p-POSSUM and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 66 publications
0
12
1
1
Order By: Relevance
“…In this subset, preoperative functional status was assessed using the American Society of Anaesthesiologists (ASA) score and the six-point Revised Cardiac Risk Index (RCRI); including high-risk surgical procedure, history of ischaemic heart disease, history of heart failure, cerebrovascular disease, insulin dependent diabetes and preoperative serum creatinine concentration ≥177 μmol/L. Other predictors of postoperative risk including body mass index (BMI) and the Glasgow Prognostic Score (GPS) [11] were collected prospectively to permit comparison with CPET data.…”
Section: Patient-level Data and Disease Descriptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this subset, preoperative functional status was assessed using the American Society of Anaesthesiologists (ASA) score and the six-point Revised Cardiac Risk Index (RCRI); including high-risk surgical procedure, history of ischaemic heart disease, history of heart failure, cerebrovascular disease, insulin dependent diabetes and preoperative serum creatinine concentration ≥177 μmol/L. Other predictors of postoperative risk including body mass index (BMI) and the Glasgow Prognostic Score (GPS) [11] were collected prospectively to permit comparison with CPET data.…”
Section: Patient-level Data and Disease Descriptorsmentioning
confidence: 99%
“…Postoperative morbidity was defined using the International Study Group [11] for Pancreatic Surgery (ISGPS) classification for post-pancreaticoduodenectomy complications of postoperative pancreatic fistula (POPF) [12] delayed gastric emptying (DGE) [13] and post-pancreaticoduodenectomy haemorrhage (PPH) [14]. Cardiac complications included acute myocardial infarction (detection of a rise in serum troponin) and electrocardiographic (ECG) changes indicative of new ischaemia; congestive cardiac failure and, serious dysrhythmia resulting in compromised tissue perfusion and primary cardiac arrest.…”
Section: Patient-level Data and Disease Descriptorsmentioning
confidence: 99%
“…More recently, there has been some evidence that the presence of an ongoing systemic inflammatory response before surgery is associated with the development of post‐operative complications in patients undergoing surgery for colorectal cancer, oesophageal cancer as well as pancreatic cancer …”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Postoperative mortality risk is typically <5% in high-volume institutions, [16][17][18][19][20][21][22][23][24] but morbidity remains high at 30-40%. [24][25][26][27][28][29][30][31][32][33] Relatively few studies have assessed the implementation of an ERAS programme following PD. 19,20,[34][35][36][37][38][39] Some studies have reported the feasibility and effect on reducing postoperative LoS and hospital costs.…”
Section: Introductionmentioning
confidence: 99%